Penerapan aplikasi quizizz sebagai media penilaian hasil belajar ips pembelajaran daring kelas iv sekolah dasar - Salsabila, Adinda Azhri; Istiyati, Siti; Kamsiyati, Siti (Didaktika Dwija Indria, 2022)
This study aims to describe the application of the Quizizz Application as a medium for assessing social studies learning outcomes in online learning according to the assessment procedure in the cognitive domain of fourth-grade students at SDN Sondakan No. 11 Academic Year 2021/2022. This research is a qualitative descriptive study. The research data source comes from interview transcripts and questionnaires for fourth-grade teacher, the fourth-grade student questionnaire, and document studies. Data collection techniques were carried out through interviews, questionnaires, and document studies. The data validity test technique used is technique triangulation and source triangulation. This study uses the data analysis model of Miles and Huberman which consists of data reduction, data presentation, and conclusion. The results of this study indicate that the implementation of the assessment using the Quizizz assessment media carried out by teacher at the planning stage of the assessment has not made a question grid and validation questions due to time constraints and the making of scoring guidelines are made at the assessment processing stage. At the stage of reporting and utilizing the results of the assessment, the teacher has not implemented remedial and enrichment due to the lack of time, then the teacher also has not made maximum use of the features contained in Quizizz, especially in the implementation of feedback.